University Student Satisfaction and Behavioural Engagement During Emergency Remote Teaching - Taşkın, Necati; Kandemir, Bülent; Erzurumlu, Kerem (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2023)
This study aimed to examine students’ online learning satisfaction in the context of emergency remote teaching. The research was carried out using a concurrent triangulation design with mixed methods. The quantitative data were collected from 2,663 students studying at different faculties/schools of a state university in Türkiye in the fall semester of the 2020–2021 academic year. Qualitative data were collected from 494 students who expressed their opinionsthrough open-ended questions or free text. Participants consisted of students who participated voluntarily according to the convenient sampling method. An e-satisfaction scale was used to determine students’ online learning satisfaction. The number of logins to the learning management system (LMS), logins to live courses, and recorded course views of students were considered to be behavioural engagement indicators. According to the findings, the students had a moderate level of satisfaction. There was a significant difference between both academic achievement and behavioural engagement of students with satisfaction levels. Students frequently mentioned these themes: longing for face-to-face education, the usefulness of the LMS, inadequate assessment, the inefficiency of online learning, technical problems, challenges of the process, and insufficient instructors. This study recommends that instructors, educational authorities, and policymakers consider online student satisfaction for a successful digital transformation in higher education.